See It Feelingly - James Savarese, Ralph (Duke University Press, 2023)
Ralph James Savarese showcases the voices of autistic readers by sharing their unique insights into literature and their sensory experiences of the world, thereby challenging common claims that people with autism have a limited ability to understand language, to partake in imaginative play, and to generate the complex theory of mind necessary to appreciate literature.